Deregulation of p27 by oncogenic signaling and its prognostic significance in breast cancer - Alkarain, Angel (BioMed Central, 2004)
p27 is a key regulator of progression from G1 to S phase. Although the gene encoding p27 is rarely mutated in human cancers, p27 is functionally inactivated in a majority of human cancers through accelerated p27 proteolysis, through sequestration by cyclin D–cyclin-dependent kinase complexes and by cytoplasmic mislocalization. Here we review mechanisms whereby oncogenic activation of receptor tyrosine kinase and Ras pathways lead to accelerated p27 proteolysis and p27 mislocalization in cancer cells. The prognostic significance of p27 in human breast cancer is also reviewed.